KONTRIBUSI TIM SUKSES SUPARMAN SUKIMAN (SUSUKI) DALAM PILKADA KABUPATEN ROKAN HULU TAHUN 2015 - Abdul Rahman; Ali Yusri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The election of regent and vice regent arranged by 2004 contitution Number 32 about Regional Goverment, which is descripted by 2005 Government Law number 6 about election, ratification, assignment and dismissal of regent and vice regent, ordered to the Election elected by people directly. Succeeding Team have important role to make strategy to make win there candidate. Succeeding Team can be said as campaign team. Succeeding Team is the organization which is arranged with effectiveness and efficiency principle in accordance with the needs and measurable results. Then each candidate must be good at choosing a Succeeding team member. Succeeding Team members in regent election should be dominated by party members. However, for strategic positions of Succeeding team, candidate should throughly select all the members of the Succeeding team and party members. Because the determination of a Succeeding team is the beginning of success of regent candidate to win the election.The purpose of this research is to know the contribution of Suparman-Sukiman (SUSUKI) secceeding team in 2016 Rokan Hulu Regent Election and to know the obstacles of secceeding team. The research method used is descriptive qualitativ. The informants in this research is Head of secceeding team and the coornitor team of supporting party.Result of this research is secceeding team of Suparman-Sukiman (SUSUKI) has give contributed greatly in Rokan Hulu Regent Election, but there are some obstacles in the implementation of program is Rokan Hulu Regency have topographical condition that is so wide that access to the other villages is takes time and subtantial funds.Keywords: Contribution, Succeeding Team, Regent Election